Importance of Psychology in Educational System - Sharapova Sabokhat Jabbarovna (Zien Journals, 2022)
All behavior and activity changes in the child during the growth of age are considered learning factors. Learning requires external (physical) and internal (mental) changes in activity and behavior that enable the achievement of a specific goal. In other words, learning is manifested in purposeful changes in external and internal activity (behavior). This article discusses the importance of psychology in the educational system
Keywords: Educational system; psychology; intelligence; mental activity